California's Contributions - Unknown (Unknown)
There is a growing belief that the free food Americans sent to Italy proved a strong factor in the recent election and that food more than anything else convinced the Italians that our proffers of friendship and aid were not mere lip service. Unquestionably the flow of letters to friends and former acquaintances were of material assistance, but those large and small contributions of food and clothing left nothing to the imagination as to how the average American felt about Italy and her problems.